Ethnobiology of wonosobo batik: Biology education reference book based on local wisdom - Susi Setianingsih; Ericka Darmawan; Setiyo Prajoko (Universitas Negeri Jakarta, 2026)
Wonosobo batik motif interprets the rich nature, the geographical conditions, and the existing culture through distinctive motifs and utilizes several plant parts as its natural dyes. Utilizing the potential of flora and fauna in batik is not yet widely known by the public due to limited information. This study aims to determine the ethnobiological profile of Wonosobo Batik and to determine the feasibility of a reference book entitled